Pemanfaatan Sampah Plastik Menjadi Paving Block Berkualitas Dan Berdaya Saing Dalam Upaya Peningkatan Produksi Dan Pendapatan - Abednego Dwi Septiadi; Eka Trupustikasari; Arif Amrulloh (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The problem that must be overcome by all parties is garbage. Society must take an active role to solve this problem. In an effort to safeguard the environment, the Maju Jaya Waste Bank has a role in sorting and processing waste. Organic waste will become fertilizer. Plastic or non-organic waste will be the raw material for the Paving Blok Prima Lestari Bumi Group. Paving Block Prima Lestari Bumi Group will process plastic waste into paving blocks. However, there are several problems faced. The problem faced by Prima Lestari partner Bumi Paving Blok, such as the lack of supply of raw materials for plastic waste, lack of operational equipment, which causes the production of paving blocks cannot maximize. The level of sales still cannot meet the target per month. Current marketing aspects are carried out by word of mouth and take part in exhibitions carried out by the local government or using social media. For Maju Jaya Garbage Bank, the problem is a large amount of operational costs to sort waste based on the type of waste. This is inversely proportional to income from processed products that are less than optimal. Some of the solutions offered to partners are several parts of training for the sale of goods, procurement of operational goods such as production machinery for paving blocks and machines that can sort waste by type to reduce operating costs.